294. Surveillance for Potential Post-Acute COVID-19 Syndrome Medical Complications in the Emergency Department (ED) – A Retrospective Longitudinal Study of ED Patients Who Had Evidence of SARS-CoV-2 Infection Versus Those Who Did Not. (4th December 2021) - Lake, Isabel; Wang, Richard C; Rothman, Richard E; Laeyendecker, Oliver; Fernandez, Reinaldo; Dashler, Gaby; Quinn, Thomas; Hsieh, Yu-Hsiang
Abstract: Background: As the COVID-19 pandemic continues, growing attention has been placed on whether patients previously infected with SARS-CoV-2 have an increased risk of developing and/or exacerbating medical complications. Our study aimed to determine whether individuals with previous evidence of SARS-CoV-2 infection prior to their current emergency department (ED) visit were more likely to present with specific clinical sign/symptoms, laboratory markers, and/or clinical complications. Methods: A COVID-19 seroprevalence study was conducted at Johns Hopkins Hospital ED (JHH ED) from March 16 to May 31, 2020. Evidence of ever having SARS-CoV-2 infection (PCR positive or IgG Ab positive) was found in 268 ED patients at this time (i.e. infected and/or previously infected). These patients were matched 1:2 to controls, by date, to other patients who attended the JHHED. Clinical signs/symptoms, laboratory markers, and/or clinical complications associated with ED visits and/or hospitalizations at JHH within 6 months after their initial ED visit was abstracted through chart review for these 804 patients. Cox proportional hazards regression analyses were performed. Results: Among 804 ED patients analyzed, 50% were female, 56% Black race, and 15% Hispanic with a mean age of 47 years. 323 (40%) patients had at least 1 subsequent ED visit and additional 70 (9%) had been admitted to JHH. After controlling for race and ethnicity, patients with evidence of current or prior COVID-19 infection were more likely to require supplemental oxygen [hazards ratio (HR) =2.53; p=0.005] and have a cardiovascular complication [HR =2.13; p=0.008] during the subsequent ED visit than the non-infected patients. Conclusion: Our findings demonstrate that those previously infected with SARS-CoV-2 have an increased frequency of cardiovascular complications and need for supplemental oxygen in ED visits in the months after their initial SARS-CoV-2 infection was detected. EDs could serve as a critical surveillance site for monitoring post-acute COVID-19 syndrome complications. Disclosures: Richard E. Rothman, PhD, MD, Chem bio (Grant/Research Support)